ROLE OF INSURANCE IN OVERCOMEING CREDIT BADGETS ON BRI UNIT LECES OF PROBOLINGGO BRANCH OFFICE - Eko Wicaksono (Universitas Islam Lamongan, 2022)
Credit agreement is an agreement between the recipient and the lender that contains provisions regarding the amount and method of repaying the loan, the purpose of using the credit, the term of the credit, the type and increase of credit guarantees, the method of withdrawing credit, interest rates and so on. Credit is the provision of money or bills that can be equal with it, based on loan agreement or agreement to pay off debts after a certain period of time with the provision of interest, rewards, or profit sharing. In the process of implementing credit there must be a variety of problems that occur, so the bank needs insurance services to protect and reduce problems that occur. The formulation of the issues to be discussed is how the business criteria can be guaranteed by credit insurance companies, whether the advantages and disadvantages of using credit insurance, and whether the role of credit insurance in overcoming bad credit. Research methods conducted using qualitative research methods, namely by collecting data collection sourced from secondary and tertiary primary data that processes funds and cannot be separated from various interpretations known as juridical empirical science with data collection techniques through interviews or research to complete the data-other data . From the results of the study found things that occur such as business criteria that can be guaranteed by credit insurance companies, and whether theadvantages and drawbacks of credit insurance and the role of credit insurancein dealing with bad loans are closely related to the benefits of purpose and function, these three words are representative of the word role which means that the thing applies or acts as the main actor . Credit insurance as an insurance business has a role in collecting public funds starting from collecting insurance premiums, providing protection to members of the public who use insurance services against the possibility of loss due to an uncertain event or to a person's life and death in accordance with article 2 of Law No. 40 of 2014 concerning Insurance Business. The insurer has protected and guaranteed in the event of problems both in the form of bad loans that occur at the these three words are representative of the word role which means that the thing applies or acts as the main actor. Credit insurance as an insurance business has a role in collecting public funds starting from collecting insurance premiums, providing protection to members of the public who use insurance services against the possibility of loss due to an uncertain event or to a person's life and death in accordance with article 2 of Law No. 40 of 2014 concerning Insurance Business. The insurer has protected and guaranteed in the event of problems both in the form of bad loans that occur at the these three words are representative of the word role which means that the thing applies or acts as the main actor. Credit insurance as an insurance business has a role in collecting public funds starting from collecting insurance premiums, providing protection to members of the public who use insurance services against the possibility of loss due to an uncertain event or to a person's life and death in accordance with article 2 of Law No. 40 of 2014 concerning Insurance Business. The insurer has protected and guaranteed in the event of problems both in the form of bad loans that occur at the providing protection to members of the public who use insurance services against the possibility of loss due to an uncertain event or to a person's life and death in accordance with article 2 of Law No. 40 of 2014 concerning Insurance Business. The insurer has protected and guaranteed in the event of problems both in the form of bad loans that occur at the providing protection to members of the public who use insurance services against the possibility of loss due to an uncertain event or to a person's life and death in accordance with article 2 of Law No. 40 of 2014 concerning Insurance Business. The insurer has protected and guaranteed in the event of problems both in the form of bad loans that occur at theBRI Unit Leces Probolinggo City Branch Office and other problem loans, which the bank feels more comfortable, as well as the customer. The customer has also received the same insurance guarantee as life insurance if he carried out the loan implementation process.